2021
DOI: 10.3390/ijerph18115776
|View full text |Cite
|
Sign up to set email alerts
|

Recovery-Stress Response of Blood-Based Biomarkers

Abstract: The purpose of this study was to investigate blood-based biomarkers and their regulation with regard to different recovery-stress states. A total of 35 male elite athletes (13 badminton, 22 soccer players) were recruited, and two venous blood samples were taken: one in a ‘recovered’ state (REC) after a minimum of one-day rest from exercise and another one in a ‘non-recovered’ state (NOR) after a habitual loading microcycle. Overall, 23 blood-based biomarkers of different physiologic domains, which address infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Regarding football, a vast number of studies conducted in male and female semi-professional and professional football players have reported values of CK as a means to assess EIMD in training and competition ( Andersson et al, 2008 ; Gravina et al, 2011 ; Rampinini et al, 2011 ; Thorpe and Sunderland, 2012 ; Gatterer et al, 2013 ; Gunnarsson et al, 2013 ; Nedelec et al, 2013 ; Silva et al, 2013 ; Souglis et al, 2015a ; Pimenta et al, 2015 ; Russell et al, 2015 ; Mohr et al, 2016 ; Bouzid et al, 2018 ; Henrique et al, 2018 ; Marques-Jimenez et al, 2018 ; Souglis et al, 2018 ; Sparkes et al, 2018 ; Botelho et al, 2020 ; Pooley et al, 2020 ; Chou et al, 2021 ; Csala et al, 2021 ; Daab et al, 2021 ; Garcia-Romero-Perez et al, 2021 ; Hacker et al, 2021 ; Khaitin et al, 2021 ; Kostrzewa-Nowak et al, 2021 ; Trecroci et al, 2021 ; Selmi et al, 2022 ). Of note, as susceptibility to EIMD is higher among players unaccustomed to eccentric exercise, returning to high-intensity training and competition from off-season and periods of recovery from injury are considered critical time points for monitoring ( Nédélec et al, 2012 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding football, a vast number of studies conducted in male and female semi-professional and professional football players have reported values of CK as a means to assess EIMD in training and competition ( Andersson et al, 2008 ; Gravina et al, 2011 ; Rampinini et al, 2011 ; Thorpe and Sunderland, 2012 ; Gatterer et al, 2013 ; Gunnarsson et al, 2013 ; Nedelec et al, 2013 ; Silva et al, 2013 ; Souglis et al, 2015a ; Pimenta et al, 2015 ; Russell et al, 2015 ; Mohr et al, 2016 ; Bouzid et al, 2018 ; Henrique et al, 2018 ; Marques-Jimenez et al, 2018 ; Souglis et al, 2018 ; Sparkes et al, 2018 ; Botelho et al, 2020 ; Pooley et al, 2020 ; Chou et al, 2021 ; Csala et al, 2021 ; Daab et al, 2021 ; Garcia-Romero-Perez et al, 2021 ; Hacker et al, 2021 ; Khaitin et al, 2021 ; Kostrzewa-Nowak et al, 2021 ; Trecroci et al, 2021 ; Selmi et al, 2022 ). Of note, as susceptibility to EIMD is higher among players unaccustomed to eccentric exercise, returning to high-intensity training and competition from off-season and periods of recovery from injury are considered critical time points for monitoring ( Nédélec et al, 2012 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
“…The initial release of IL-6 usually precedes a less pronounced increase in the levels of different pro- and anti-inflammatory cytokines, with IL-1β and tumor necrosis factor α (TNF-α) being the most widely studied ( Pedersen et al, 1998 ; Pedersen, 2000 ). In particular, concentrations of IL-1β have been observed to increase during post-match ( Ispirlidis et al, 2008 ; Mohr et al, 2016 ; Jatene et al, 2019 ) and throughout the competitive season ( Nobari et al, 2021 ) in elite football players, yet studies are scarce and inconsistent changes in circulating values have been reported ( Andersson et al, 2010a ; Hacker et al, 2021 ). In the same vein, TNF-α is another pro-inflammatory cytokine, which is speculated to play a role in muscle regeneration ( Yang and Hu, 2018 ), and whose serum levels have been documented to peak immediately after a football match, with postgame concentrations being ≈100%–200% higher when compared to pre-game values ( Souglis et al, 2015a ; Koziol et al, 2020 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
“…Маркерами пошкодження м'язів можуть виступати креатинкіназа, креатинін, лактатдегідрогеназа, міоглобін, тропонін, аспартатамінотрансфераза [4,6,19]. Тому вивчення сучасних лабораторних маркерів структурно-функціонального порушення м'язової тканини у спортсменів, які відображають енергетичний обмін, ураження паравертебральних м'язів [8], або, навпаки, є показником працездатності організму та функціональної активності м'язів [14,18,24] має незаперечливе практичне значення для сучасної спортивної медицини.…”
Section: вступunclassified
“…First of all, we and other scientists were able to identify several markers in human serum which demonstrated a certain suitability and reliability as biomarkers for exercise response and stress-recovery cycles. These markers include cytokines, such as interleukin (IL-)1β, IL-1 receptor antagonist, IL-6, IL-8, IL-17A, and Interferon gamma (IFN-γ), chemokines, such as CC-chemokine ligand 2 (CCL-2), matrix metallopeptidase (MMP), such as MMP-9, matrix and membrane proteins, such as secreted protein acidic and rich in cysteine (SPARC), and Cluster of differentiation (CD163), Ca 2+ -binding proteins, such as S100A8, S100A9, and S100B, growth factors, such as Brain-derived neurotrophic factor (BDNF), and enzymes such as myeloperoxidase (MPO) (Nieman et al 2018 ; Reichel et al 2020 ; Hacker et al 2021 ). Concerning possible concentration differences between serum and plasma a closer examination using Bland–Altman analyses revealed that for some cytokines such as IL-1β, IL-6, and IL-8 the agreement was moderately good between both media (Parkitny et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%